SEQUÊNCIA DIDÁTICA PARA O ENSINO DE QUIMICA ORGÂNICA UTILIZANDO O TEMA PLANTAS - Lima, Andréia Boeno de (2016)
This research aimed to develop and implement a Didactic Sequence for Organic Chemistry Teaching using the theme Plants and Collaborative Groups, which was based on Vygotsky Learning Theory proposes that the student learns through its interaction with the social environment and with their culture, and learning to occur following this theory in this work was done using the methodology of Education by Research and Collaborative Groups, aimed at interaction among students and build their own knowledge with the teacher in this process one mediator of knowledge. Sequence Didactic has 6 teaching units, and these units are active principles of research activities of some plants known by students, assembly of organic molecules with alternative materials, presentation of current issues seminars as biopiracy, GM products and use of resources natural, and these activities with students of the 3rd year of high school. Application of Sequence Didactic allowed students learn organic functions without decorate them, known plants of your day to day, its importance, applications and implications, and the methodology focused on research and collaborative groups has shown that learning was achieved a more dynamic, continuous, focused on the student and covering various aspects such as speech, writing, teamwork.